On-iceberg autonomous phase-sensitive radar (ApRES) data from 10-day deployment in Sermilik Fjord, Southeast Greenland, 2019 ... - Schild, Kristin; Vankova, Irena; Sutherland, David; Nicholls, Keith (NSF Arctic Data Center, 2024)
Data collection and processing methods are outlined in Schild, K. M., I. Vankova, D. A. Sutherland and K. W. Nicholls (2024), Deriving Iceberg Ablation Rates using an On-Iceberg ApRES, Annals of Glaciology, 65, doi:10.1017/aog.2024.35. Paper abstract: The increase in iceberg discharge into the polar oceans highlights the importance of understanding how quickly icebergs are deteriorating and where the resulting freshwater injection is occurring. Recent advances in quantifying iceberg deterioration through combinations of modeling, remote sensing, and direct in situ measurements have successfully calculated overall ablation rates, and surface and sidewall ablation; however, in situ measurements of basal melt rates have been difficult to obtain. Radar has successfully measured iceberg thickness, but repeat measurements, which would capture a change in iceberg thickness with time, have not yet been collected. Here we test the applicability of using an on-iceberg autonomous phase-sensitive radar (ApRES) to ...